2007
DOI: 10.1086/522296
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the First Gravitational Microlensing Event in a Sparse Stellar Field: The Tago Event

Abstract: We report the observation of the first gravitational microlensing event in a sparse stellar field, involving the brightest (V ¼ 11:4 mag) and closest ($1 kpc) source star to date. This event was discovered by an amateur astronomer, A. Tago, on 2006 October 31 as a transient brightening, by $4.5 mag during a $15 day period, of a normal A-type star (GSC 3656-1328) in the Cassiopeia constellation. Analysis of both spectroscopic observations and the light curve indicates that this event was caused by gravitationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Observations along the lines that we discuss will constrain the nomad population of the disc relative to the bulge, and will also more generally improve the star-star microlensing event rate in the disc and the solar neighbourhood, about which very little is now known (Fukui et al 2007;Gaudi et al 2008;Rahal et al 2009). Further, they will improve our understanding of the mass function of lowmass brown dwarfs and super-Jupiters, and the distinction between these classes of objects (Spiegel, Burrows & Milsom 2011).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Observations along the lines that we discuss will constrain the nomad population of the disc relative to the bulge, and will also more generally improve the star-star microlensing event rate in the disc and the solar neighbourhood, about which very little is now known (Fukui et al 2007;Gaudi et al 2008;Rahal et al 2009). Further, they will improve our understanding of the mass function of lowmass brown dwarfs and super-Jupiters, and the distinction between these classes of objects (Spiegel, Burrows & Milsom 2011).…”
Section: Discussion a N D C O N C L U S I O N Smentioning
confidence: 99%
“…Second, Gaudi et al (2008b) analyzed a microlensing event of a nearby (1 kpc), bright (V = 11) source serendipitously discovered by an amateur astronomer hunting for comets, finding that it was most likely a low-mass star or brown dwarf moving at roughly 100 km s −1 . Based on the low rate of such events (and the non-systematic character of the search), they concluded that they were "probably lucky ... but perhaps not unreasonably so" to have found this event (see also Fukui et al 2007). Finally, Faherty et al (2009) found 14 high-velocity objects in a sample of 332 M, L, and T dwarfs, which are consistent with thickdisk or halo kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lensing of stars in our own Galaxy will also be observed. To illustrate, we note that limited monitoring has already discovered the lensing of an A0 star just one kpc away by an unknown intervening mass (Fukui et al 2007;Gaudi et al 2008).…”
Section: What Does Lsst Bring To These Studies?mentioning
confidence: 99%